Teaching diversity, questioning representation - Sarah Sinwell (Alphaville: Journal of Film and Screen Media, 2022)
This paper creates a taxonomy of representation that includes suggestions for how students might be more inclusive in terms of how they think about representations of diversity in their own media and filmmaking practices. To this end, I argue that there are six modes of thinking about how to analyse and interrogate representation in the media: 1) search for presence, 2) seek out positive representation, 3) create complex and layered characters, 4) consider casting, crew, consulting, and mentoring (including below-the-line), 5) focus on intersectionality, empathy, and empowerment, 6) interrogate your choices. This paper will explain how students may use these maxims and modes of thinking as a means of mapping out how they might move towards more inclusive representation in both their own productions as well as their mediamaking practices by using examples from documentaries such as The Celluloid Closet (Rob Epstein and Jeffrey Friedman, 1995), Ethnic Notions (Marlon Riggs, 1987), The Slanted Screen (Jeff Adachi, 2006), Reel Arabs (Jeremy Earp and Sut Jhally, 2006), Reel Injun (Neil Diamond, Catherine Bainbridge, Jeremiah Hayes, 2009), Latinos Beyond Reel (Chyung Sun and Miguel Parker, 2012), Horror Noire: A History of Black Horror (Xavier Burgin, 2019), and Disclosure (Sam Feder, 2020).